2020
DOI: 10.1038/s41598-020-62394-0
|View full text |Cite
|
Sign up to set email alerts
|

Visual appearance of the virtual hand affects embodiment in the virtual hand illusion

Abstract: Body ownership (the feeling that one's body belongs to oneself) is commonly studied with Rubber hand illusion (RHI) paradigm that allows inducing a temporary illusory feeling of ownership of a life-sized rubber hand. However, it remains unclear whether illusory ownership of the fake hand relies on the same mechanisms as ownership of one's own real hand. Here, we directly compared ownership of the own hand (OH) and fake hand (FH) in the same set of conditions within immersive virtual reality. We obtained behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 59 publications
2
46
0
Order By: Relevance
“…Embodiment depends on the quality of certain factors such as appearance or point of view in the VR environment [ 20 ]. Some studies suggested that the detailed appearance of the body contributed to the construction of the body image in VR [ 21 ]. Kim also demonstrated the importance of the correspondence between the properties of the real human body and the adaptation made in VR to obtain the best possible incarnation and therefore the best illusion [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Embodiment depends on the quality of certain factors such as appearance or point of view in the VR environment [ 20 ]. Some studies suggested that the detailed appearance of the body contributed to the construction of the body image in VR [ 21 ]. Kim also demonstrated the importance of the correspondence between the properties of the real human body and the adaptation made in VR to obtain the best possible incarnation and therefore the best illusion [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The visual representation of the hands also contributes to the embodiment as seen in the work of Pyasik et al [13], which shows us that a realistic hand representation feels slightly more ownership over the hand than a fake hand representation. However, an object or no hand looking like a selector had the participants feel minor ownership.…”
Section: B Visual Representation Of the Handsmentioning
confidence: 88%
“…To prevent a possible uncanny valley effect by having realistic bodies with inconsistent realism [44], [45], which might occur with transparency and changing the hand color, we choose to use a glove type of representation for the hands instead of a realistic version. A non-realistic hand but yet still hand looking like representation barely affects the sense of ownership over the hand [10], [13], [14] and therefore will not influence the test results.…”
Section: Visual Aspect Of the Handmentioning
confidence: 99%
“…Body continuity is a significant factor in the strength of the rubber hand illusion that was not implemented in our setup but may have increased the strength of the illusion (Perez-Marcos et al, 2012;Tieri et al, 2015). The level of realism and congruence in appearance can also impact the strength of the illusion, with gender (Schwind et al, 2017), race (Lira et al, 2017), and overall appearance (Pyasik et al, 2020) each impacting measurements of sense of embodiment when manipulated. We would have likely increased the strength of the illusion along with its impact on sense of embodiment if we had added a wrist and arm to the virtual hand, along with improving the realistic appearance of the hand and adjusting its gender and race for each participant.…”
Section: Discussionmentioning
confidence: 99%